Mechanisms of manganese-induced neurotoxicity and the pursuit of neurotherapeutic strategies - Pajarillo, Edward; Nyarko-Danquah, Ivan; Digman, Alexis; Multani, Harpreet Kaur; Kim, Sanghoon; Gaspard, Patric; Aschner, Michael; Lee, Eunsook (Frontiers in Pharmacology, 2022)
Chronic exposure to elevated levels of manganese via occupational or environmental settings causes a neurological disorder known as manganism, resembling the symptoms of Parkinson’s disease, such as motor deficits and cognitive impairment. Numerous studies have been conducted to characterize manganese’s neurotoxicity mechanisms in search of effective therapeutics, including natural and synthetic compounds to treat manganese toxicity. Several potential molecular targets of manganese toxicity at the epigenetic and transcriptional levels have been identified recently, which may contribute to develop more precise and effective gene therapies. This review updates findings on manganese-induced neurotoxicity mechanisms on intracellular insults such as oxidative stress, inflammation, excitotoxicity, and mitophagy, as well as transcriptional dysregulations involving Yin Yang 1, RE1-silencing transcription factor, transcription factor EB, and nuclear factor erythroid 2-related factor 2 that could be targets of manganese neurotoxicity therapies. This review also features intracellular proteins such as PTEN-inducible kinase 1, parkin, sirtuins, leucine-rich repeat kinase 2, and α-synuclein, which are associated with manganese-induced dysregulation of autophagy/mitophagy. In addition, newer therapeutic approaches to treat manganese’s neurotoxicity including natural and synthetic compounds modulating excitotoxicity, autophagy, and mitophagy, were reviewed. Taken together, in-depth mechanistic knowledge accompanied by advances in gene and drug delivery strategies will make significant progress in the development of reliable therapeutic interventions against manganese-induced neurotoxicity.